GranDIHC-BR 2025-2035 - GC5 - Human-Data Interaction, Data Literacy and Usable Privacy - Coleti, Thiago Adriano; Divino, Sthéfano Bruno Santos; Salgado, André de Lima; Zacarias, Rodrigo Oliveira; Saraiva, Juliana de Albuquerque Gonçalves; Gonçalves, Diego Addan; Morandini, Marcelo; Santos, Rodrigo Pereira dos (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
The phenomenon of the data deluge has brought to light issues related to the perception of the goals and impacts of data usage in individuals' daily lives. The manipulation of personal data, common in various application domains, suggests that it is practically impossible to interact with any technological resource without personal data being processed. This fact promotes the creation, improvement, and/or implementation of data usage regulations, such as Brazil's General Data Protection Law (LGPD), and has led to the emergence of a research and development area known as Human-Data Interaction (HDI). Work in HDI has diverse objectives, but concerns about data subjects and methods and techniques that support the development of products and services within HDI concepts are more common. Regarding these issues, it has been noted that the literature offers limited perspectives on HDI, Data Literacy, and Usable Privacy. In this sense, there is a need to explore aspects related to the protection of personal data in HDI. This involves strategies to promote data transparency and privacy while enhancing data literacy. In this scenario, this paper presents and discusses the Grand Challenge for the Human-Computer Interaction (HCI) field: developing methods and techniques that promote HDI with Data Literacy and Usable Privacy. This challenge was proposed in light of the need to promote the capacity for people to interact with data applications in a sustainable, educational, and secure manner to ensure that individuals/data subjects can enjoy all the benefits of these applications while privacy, security, and freedom can be managed and guaranteed. Additionally, the article also presents a research agenda detailing necessary actions, required resources, main difficulties, ways to evaluate results and progress, and ethical issues to guide the HCI community in addressing this Grand Challenge.